KONTRIBUSI PERSEPSI KETERAMPILANMENGAJAR DAN MOTIVASI BELAJAR TERHADAPHASIL BELAJAR - Ahmad Sidik; Sukaya Sukaya (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2019)
The background of this research is the problem of low learning outcomes in training Menerapkan Dasar-Dasar Elektronika, which 31,28% of students scored under lower minimum limit value (KKM). The purposes of this research are to reveal the contribution of students' perceptions of teacher teaching skills and the motivation to learn individually or jointly on learning outcomes. Keywords: students' perceptions of teacher teaching skills, motivation to learn, Learning Outcomes.The Occupant of this reseach come  to 99 students and the number of sample is 49 students at the class X SMKN 1 Padang. The sampling technique is Simple Random Sampling. Data on student learning outcomes obtained from subject teachers Menerapkan Dasar-Dasar lektronika. While data on students' perceptions of teacher teaching skills and the motivation to learn collected through questionnaires distributed to students by using a Likert scale that has been tested for validity and reliability.The result showed that (1) students' perceptions of teacher teaching skills and the motivation to learn jointly contribute significantly to student learning outcomes SMKN 1 Padang amounting to 37,99%. (2) students' perceptions of teacher teaching skills contribute significantly to student learning outcomes SMKN 1 Padang amounted to 23,88%, (3) motivation to learn contribute significantly to student learning outcomes SMKN 1 Padang amounted to 26,39%, so it can be concluded that students' perceptions of teacher teaching skills and the motivation to learn contribute to student learning outcomes in SMKN 1 Padang. Keywords: students' perceptions of teacher teaching skills, motivation to learn, student learning outcome.